The efficacy of synthetic food baits in capturing Red Palm Weevil, Rhynchophorus ferrugineus (coleoptera: curculionidae) in campus area of Universiti Malaysia Terengganu - Haris, M.H.; Nang, M.L.S.; Chuah, T.S.; Wahizatul, A.A. (Pusat Sistematik Serangga ,UKM, 2014)

(untitled)
Red Palm Weevil (RPW), Rhynchophorus ferrugineus is known as one of the most destructive pest of major cultivated palm industries such as coconut palm (Cocos nucifera), date palm (Phoenix daciylifera) and oil palm (Elaeis guineensis). In early 2007, RPW was first recorded in some small coconut plantations in Setiu, Terengganu by Department of Agriculture (DOA). One of the cui rent methods to control the RPW is the use of the pheromone traps instead of chemical pesticides. In this current study, a 60 days experiment of pheromone mass trapping using synthetic food baits was conducted around Universiti Malaysia Terengganu (UMT) campus to evaluate the effectiveness of synthetic food baits in capturing RPW. A number of 164 individuals of RPW were captured in this study. E2 treatment (ethylene glycol) recorded the highest number of trapped RPW with 52 individuals (10.4 individuals/trap), followed by El treatment (ethyl acetate), E3 treatment (ethanol) and control which were 48 individuals (9.6 individuals/trap), 44 individuals (8.8 individuals/ trap) and 20 individuals (4 individuals/trap) respectively. However, there was no significant difference between total numbers of trapped RPW with the types of treatment (F=1.174, df=3, p=4.449). Interestingly, the sex ratio of trapped adults was clearly female biased (4 female: 1 male) as there was significant difference between the sexes (-4=4.699, df=19, p= 0.000). This study has showed that palm esters could be used as potential synthetic food bait in pheromone trapping system of RPW which is suitable to be applied in dry or wet monsoon seasons.